Pengaruh Strategi Inovasi Terhadap Keunggulan Bersaing di Industri Kreatif (Studi Kasus UMKM Bidang Kerajinan Tangan di Kota Bandung) - Tintin Suhaeni (Jurnal Riset Bisnis dan Investasi, 2018)
The creative industry is one of sector that has rapid development in Indonesia, especially in Bandung. The part of this sector that tends to decrease every year or have smallest development level is Handicrafts. Although the number of businessman in this part is less than in food and beverage part, the competition between them is also fierce. The businessman should be the one who can decide the proper competitive strategy to survive in this competition. The other way to do to win the competition is applying innovation strategy towards the product so that it can be different from our competitor products and attract more customers. This research determined the relationship between innovation strategy and competitive advantage in the UKM handicraft business in Bandung. Linear regression will be used to determine this relationship.